THE EFFECT OF VIDEO DISPLAYING ON STUDENTS’ KNOWLEDGE ABOUT HIV/AIDS - Samsriyaningsih Handayani; Ika Dwi Martanti (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: Human immunodeficiency virus (HIV) is a virus that weakens the immune system and ultimately causes acquired immunodeficiency syndrome (AIDS). Based on the integrated biological and behavioral survey (IBBS) in 2015, adolescents' knowledge regarding the correct understanding of HIV prevention was still low. Knowledge is important as a first step towards HIV / AIDS prevention among adolescents. One of the steps to overcome this problem is by disseminating knowledge and information through lecture. Methods: The research was conducted at SMK 17 Agustus 1945 Surabaya. Data collection is carried out in February 2020 – January 2021. This type of research was quasi experimental. The sampling method used was consecutive sampling. The sample size was 32 respondents. Providing material is done online using zoom cloud meetings. The pretest and posttest data collection was done by students online using google form. The analysis in this study used univariate and bivariate analysis. The data collected and processed were then analyzed using the Chi-square test. Analyses: The results of the analysis test in the control group obtained a p-value of 0.941 while in the intervention group a p-value of 0.699 was obtained. Conclusion: There is no difference in knowledge of adolescents about HIV / AIDS in the control and intervention groups. Keywords: knowledge, adolescents, HIV / AIDS